2016
DOI: 10.3233/wor-162342
|View full text |Cite
|
Sign up to set email alerts
|

Accompanying citizen of persons with traumatic brain injury in a community integration project: An exploration of the role

Abstract: Five principles drawn from the results will help oversee this practice more efficiently and limit the mental health risks of accompaniers. These findings may permit further development of this type of program for people living with disabilities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 13 publications
4
6
0
Order By: Relevance
“…Moreover, as outlined in the current study and the one by Therriault & Samuelson [26], they increased their self-esteem and self-satisfaction. Through the personalized assistance process, the attendants felt useful [28] and valued by the older adults [26]. The lack of de ned boundaries for assistance affected the attendants' assistance experience.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Moreover, as outlined in the current study and the one by Therriault & Samuelson [26], they increased their self-esteem and self-satisfaction. Through the personalized assistance process, the attendants felt useful [28] and valued by the older adults [26]. The lack of de ned boundaries for assistance affected the attendants' assistance experience.…”
Section: Discussionsupporting
confidence: 83%
“…The ve other articles are about the same attendants providing the APIC in 2009-2011 to adults with TBI and, instead of addressing an overall vision of the experience, focused speci cally on its impact on the attendants' mental health [25]. The majority of attendants reported personal bene ts from their personalized assistance, such as the satisfaction of helping others and feeling useful when highlighting the abilities of adults with TBI [26], but these bene ts were not detailed further. These articles emphasized that personalized assistance was a source of pleasure for attendants despite the absence of clear boundaries de ning their role during the APIC [27].…”
Section: Personalized Assistancementioning
confidence: 99%
“…In accordance with the challenges mentioned in the current study, Therriault and colleagues [24,28] reported similar assistance experiences by attendants regarding certain personality or behavioral traits in older adults, their lack of motivation, and their refusal to participate in social activities, all of which compromised their peer relationships or their social integration. According to other studies [39,40] and the current ndings, these challenges could be related to a fear of being judged by peers.…”
Section: Discussionsupporting
confidence: 83%
“…Using creative arts rather than the APIC, one article highlighted that, while helping isolated older adults, attendants experienced positive repercussions [23], but these were not speci ed. The ve other articles are about the same attendants providing the APIC in 2009-2011 to adults with TBI and, instead of addressing an overall vision of the experience, focused speci cally on its impact on the attendants' mental health [24]. The majority of attendants reported personal bene ts from their personalized assistance, such as the satisfaction of helping others and feeling useful when highlighting the abilities of adults with TBI [25], but these bene ts were not detailed further.…”
Section: Personalized Assistancementioning
confidence: 99%
“…Using creative arts rather than the APIC, one article highlighted that, while helping isolated older adults, attendants experienced positive repercussions [24], but these were not specified. The five other articles are about the same attendants providing the APIC in 2009-2011 to adults with TBI and, instead of addressing an overall vision of the experience, focused specifically on its impact on the attendants' mental health [25]. The majority of attendants reported personal benefits from their personalized assistance, such as the satisfaction of helping others and feeling useful when highlighting the abilities of adults with TBI [26], but these benefits were not detailed further.…”
Section: Personalized Assistancementioning
confidence: 99%